Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have a question. Given a biconditional statement of the following form:

Show $p$ if and only if $q$ or $s$.

I was confused as to how to proceed.

In one direction of assuming $p$ is true, is it suffice to show $q$ is true? Or do I also need to consider if $p$ holds, then $s$ is true?

For the other direction, do I need to show two things: Assume $s$ is true and deduce $p$ and also assume $q$ and deduce that $p$ is true?

Thanks for the clarification.

share|cite|improve this question
up vote 4 down vote accepted

For the direction $p\to q\lor s$, you need to show that if $p$ is true, then at least one of $q$ and $s$ is true. If you can show that $p$ always implies $q$, then you don't need to worry about $s$ at all.

You are correct about how to prove the other direction, $(q\lor s)\to p$: show that $q\to p$ and $s\to p$. Alternatively, you can try to prove the contrapositive of $(q\lor s)\to p$, since it's logically equivalent: $\lnot p\to\lnot(q\lor s)$, or, using De Morgan's laws, $\lnot p\to(\lnot q\land\lnot s)$.

share|cite|improve this answer
Thanks, Brian. That helped me a lot. – MathNewbie May 4 '12 at 0:24

A common way to prove $p\to(q\lor s)$ is to convert $q\lor s$ to $\neg q\to s$ or $\neg s\to q$, and then prove $p\to(\neg q\to s)$, which is equivalent in turn to $(p\land \neg q)\to s$.

Informally, this argument is usually phrased by saying something like:

"Assume $p$; if $q$ holds, then we are done, so assume that $q$ does not hold. <stuff> hence $s$ holds, and we are done."

That is, you may assume both $p$ and the negation of one of $q$ and $s$, and prove the other from among $q$ and $s$. This is equivalent to proving $p\to(q\lor s)$.

Of course, if you can prove that $p\to q$, then since $q\to q\lor s$ is true, the two implications together give you $p\to(q\lor s)$.

share|cite|improve this answer
Thanks for the insight, Arturo. ;) – MathNewbie May 5 '12 at 6:39

Essentially, you need to show three things:

$$p \rightarrow q\text{ or }s$$ $$q \rightarrow p$$ $$s \rightarrow p$$

For the first one, if you like, you can equivalently show: $$p\text{ and ~}q \rightarrow s$$ or $$p\text{ and ~}s \rightarrow q$$ But you only need to show one of these two and ($p \rightarrow q\text{ or }s$), as they all imply each other.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.